الوسائل القضائية لاكمال النقص في قواعد القانون الدولي الخاص دراسة تحليلية مقارنة - حسن, أ.د محمد جلال; الله, م.م كانياو احمد فتح (Sulaimani Journal for Humanities, 2023)
According to the principle of separation of powers, the judiciary is obliged to apply the law, and since the law is a set of legal rules whose main source is legislation, and the legislation is described as incomplete and flawed, given the inability of the legislator to take stock of most of the developments and developments of life and predict them, no matter how wise he is, and the judge is obligated to decide on the cases before him, whether there is A legal rule or not, according to Article (30) of the Iraqi Civil Procedure Law No. (83) for the year 1969, so the judiciary resorts to means to support the deficiency in the legal rules. And in the scope of international private relations, due to the absence of an independent law regulating this branch of the law, with the exception of some provisions in separate laws, which makes it difficult for the judiciary to decide disputes involving a foreign element, and for this reason we discussed the means that the judiciary uses in terms of ruse and discretion in addition to international principles The most common, and its business controls.